2013
DOI: 10.1152/ajpheart.00054.2013
|View full text |Cite
|
Sign up to set email alerts
|

Aging attenuates the protective effect of ischemic preconditioning against endothelial ischemia-reperfusion injury in humans

Abstract: Reperfusion is mandatory after ischemia but also triggers ischemia-reperfusion (I/R) injury. Ischemic preconditioning (IPC) can limit endothelial I/R injury. Nonetheless, translation of IPC to the clinical arena is often disappointing. Since application of IPC typically relates to older patients, efficacy of IPC may be attenuated with aging. Our objective was to examine the impact of advanced age on the ability of IPC to protect against endothelial dysfunction due to I/R injury. We included 15 healthy young (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 38 publications
8
49
0
Order By: Relevance
“…Therefore, these lower levels of SOD activity following acute exercise in older adults, compared to young, could help explain the lack of protection from exercise against the oxidative challenge. These data are supported in rat and human models where aging attenuates the benefits of different forms of ischemic preconditioning against an I/R injury (Fenton et al 2000;van den Munckhof et al 2013).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Therefore, these lower levels of SOD activity following acute exercise in older adults, compared to young, could help explain the lack of protection from exercise against the oxidative challenge. These data are supported in rat and human models where aging attenuates the benefits of different forms of ischemic preconditioning against an I/R injury (Fenton et al 2000;van den Munckhof et al 2013).…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, preconditioning with blood pressure cuff at 200 mmHg did not alter the response of flow-mediated dilation of the brachial artery in older adults, whereas in young adults, there was a significant difference in endothelial function with preconditioning (van den Munckhof et al 2013). Reasons for this increased rate of mortality and lack of preconditioning in older adults is not well understood; however, specific interest in cardiac protection has been placed on heat shock proteins, nitric oxide, and antioxidant enzymes (specifically SOD) due to cardiac protective properties and to further assess the mechanisms of age-associated decrease in the ability to handle I/R injury (Hamilton et al 2001;Lennon et al 2004;Starnes and Taylor 2007).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 1996, Abete et al [48] reported that the preconditioning hormetic dose response became profoundly diminished in elderly rats. This striking observation was confirmed and extended to other biological models and to humans via clinical as well as epidemiological studies [49]. It was also extended to biological systems beyond the initial work in cardiovascular systems.…”
Section: Hormesis: In Life and Deathmentioning
confidence: 59%
“…Hence, we cannot determine whether an older population at high cardiovascular risk may show comparable sympathetic buffering response to RIPC following an ischemic injury. This issue was raised in a previous study showing that older age is associated with an abolished effect of RIPC to protect against endothelial dysfunction after IR in the brachial artery (34). In addition, older age and increased cardiovascular risk are typically associated with altered sympathetic nervous function at rest and during physiological challenges (14).…”
Section: Discussionmentioning
confidence: 99%